Chronic Dengue Virus Panencephalitis in a Patient with Progressive Dementia with Extrapyramidal Features. Issue 5 (11th September 2019) - Johnson, Tory P.; Larman, H. Benjamin; Lee, Myoung‐Hwa; Whitehead, Stephen S.; Kowalak, Jeffrey; Toro, Camilo; Lau, C. Christopher; Kim, Juyun; Johnson, Kory R.; Reoma, Lauren B.; Faustin, Arline; Pardo, Carlos A.; et al.
Abstract : Objective: To determine the underlying etiology in a patient with progressive dementia with extrapyramidal signs and chronic inflammation referred to the National Institutes of Health Undiagnosed Diseases Program. Methods: Extensive investigations included metabolic profile, autoantibody panel, infectious etiologies, genetic screening, whole exome sequencing, and the phage‐display assay, VirScan, for viral immune responses. An etiological diagnosis was established postmortem. Results: Using VirScan, enrichment of dengue viral antibodies was detected in cerebrospinal fluid as compared to serum. No virus was detected in serum or cerebrospinal fluid, but postmortem analysis confirmed dengue virus in the brain by immunohistochemistry, in situ hybridization, quantitative polymerase chain reaction, and sequencing. Dengue virus was also detectable by polymerase chain reaction and sequencing from brain biopsy tissue collected 33 months antemortem, confirming a chronic infection despite a robust immune response directed against the virus. Immunoprofiling and whole exome sequencing of the patient did not reveal any immunodeficiency, and sequencing of the virus demonstrated wild‐type dengue virus in the central nervous system. Interpretation: Dengue virus is the most common arbovirus worldwide and represents a significant public health concern. Infections with dengue virus are usually self‐limiting, and chronic dengue infections have not been previously reported. Our findings suggest that dengue virus infections may persist in the central nervous system causing a panencephalitis and should be considered in patients with progressive dementia with extrapyramidal features in endemic regions or with relevant travel history. Furthermore, this work highlights the utility of comprehensive antibody profiling assays to aid in the diagnosis of encephalitis of unknown etiology. ANN NEUROL 2019;86:695–703